Development and testing of a Long Gage Strain (LGS) sensor for concrete structure instrumentation - Ayranci, Cagri (University of Ottawa (Canada), 2005)
Reinforced Concrete (RC) is the most commonly used structural material in civil engineering applications. RC structures have long term service lives under normal loading conditions; however, overload due to misuse or statistically remote events such as earthquakes may create damages that, if not detected on time, may eventually cause failure. Hence, it is important to monitor RC structures to take necessary precautions and save human lives. A L&barbelow;ong G&barbelow;age S&barbelow;train (LGS) sensor has been developed to monitor these structures. While it has been developed with concrete applications in mind, the new sensor can be used in a variety of applications, including measuring strains in pipelines, steel structures, and the like. The proposed sensor system has very low cost compared to the commercially available competing systems. Prototypes of the proposed strain sensors have been built and tested to calibrate the sensors and to prove their accuracy, repeatability, and to assess their reliability prior to in-situ concrete experiments. In-situ tests of the proposed sensors embedded into a reinforced concrete beam have been carried out. The steel rebars in the beam are also instrumented with commercial short gage length strain gages in order to compare the strain outputs of the strain gages to that of the proposed strain sensor. Results prove the accuracy, and reliability of the proposed strain sensor.
Keywords: Engineering, Civil.; Engineering, Mechanical.